2017
DOI: 10.1080/13607863.2017.1364344
|View full text |Cite
|
Sign up to set email alerts
|

The family caregiver experience – examining the positive and negative aspects of compassion satisfaction and compassion fatigue as caregiving outcomes

Abstract: Findings suggest that despite high caregiver burden and moderate compassion fatigue, family caregivers are able to provide care and find satisfaction in the role. This study supports the use of compassion fatigue and compassion satisfaction as alternative or additional outcomes to consider in future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
83
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(95 citation statements)
references
References 28 publications
10
83
0
1
Order By: Relevance
“…A study on caregivers from North Carolina, US, showed those giving care to individuals with chronic illness reported high levels of fatigue concepts of burnout (59%) [27]. In our study population, a staggering 66.8% of all caregivers and 79.1% of high-burden caregivers reported experiencing general fatigue during the past three months ( Table 2).…”
Section: Discussionmentioning
confidence: 63%
“…A study on caregivers from North Carolina, US, showed those giving care to individuals with chronic illness reported high levels of fatigue concepts of burnout (59%) [27]. In our study population, a staggering 66.8% of all caregivers and 79.1% of high-burden caregivers reported experiencing general fatigue during the past three months ( Table 2).…”
Section: Discussionmentioning
confidence: 63%
“…Caregiving responsibilities are associated with a variety of stress-related outcomes [77] that include burnout, chronic health problems, deteriorating self concept, and decline in emotional well-being [78][79][80]. A recent review shows caregiving for a person with dementia is significantly associated with psychological stress and physical ill-health [29] and that specific features of Alzheimer's disease such as aggression, sleep disturbance, and depression negatively impact the physical and mental wellbeing of FCs [81].…”
Section: Discussionmentioning
confidence: 99%
“…Caregiving responsibilities are associated with a variety of stress-related outcomes [77] that include burnout, chronic health problems, deteriorating self concept, and decline in emotional well-being [78][79][80]. A recent review shows caregiving for a person with dementia is significantly associated with psychological stress and physical ill-health [29] and that specific features of Alzheimer's disease such as aggression, sleep disturbance, and depression negatively impact the physical and mental wellbeing of FCs [81].…”
Section: Discussionmentioning
confidence: 99%